Brachytherapy for the urologist: A multidisciplinary team update for 2019. (September 2019) - Teixeira, Helen; Kang, Myungkuk; Lees, Kathryn; Beesley, Sharon; Edwards, Albert; Henderson, Alastair
Brachytherapy is a well-established treatment for localised prostate cancer. Urologists are often tasked with discussing all available treatment options with the newly diagnosed patient. Unlike radical prostatectomy and external beam radiotherapy, knowledge of brachytherapy may be limited. The aim of this article is to provide an up-to-date guide on patient selection, modern brachytherapy techniques and the management of side effects, such that the core urologist can be more confident in both discussing initial treatment options and the long-term management of brachytherapy patients. Level of Evidence: Level 5 - review article